2004
DOI: 10.1111/j.1600-0668.2004.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative air ions created by water shearing improve erythrocyte deformability and aerobic metabolism

Abstract: The paper shows that negative air ions created by water shearing method improve aerobic metabolism only during a 1-h exposure, which may be caused by improvement of erythrocyte deformability, but negative air ions created by corona discharge have no effects. A potential mechanism is that negative air ions enter the circulating blood via the lungs and electrons of these ions are delivered to the plasma protein. Why negative air ions created by corona discharge have no effects is considered that water binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
0
33
2
1
Order By: Relevance
“…In nature, NAI can be generated by the minute shearing of water droplets, radioactive components of soil, cosmic radiation, ultraviolet rays, coronal discharge or lightning, and forests (Krueger and Reed 1976;Yates et al 1986;Iwama 2004). Of these, forests are the main continuous natural source of NAI (Wang and Li 2009), because leaf tips have a photoelectric effect during photosynthesis, which are able to promote electrolysis and produce large quantities of NAI (Tikhonov et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…In nature, NAI can be generated by the minute shearing of water droplets, radioactive components of soil, cosmic radiation, ultraviolet rays, coronal discharge or lightning, and forests (Krueger and Reed 1976;Yates et al 1986;Iwama 2004). Of these, forests are the main continuous natural source of NAI (Wang and Li 2009), because leaf tips have a photoelectric effect during photosynthesis, which are able to promote electrolysis and produce large quantities of NAI (Tikhonov et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The physical characterization of waterfall-generated ions was part of a randomized controlled clinical study, which focused on the influence of these waterfall generated ions and aerosols on human lung function. Physiological and medical effects of ions and waterfalls has been described (Iwama, 2004;Yamada et al, 2005;Takahashi et al, 2008), but interpretation of specific health-related effects still require a thorough physical characterization. In the present study we analyzed five waterfalls with respect to their distribution of ions.…”
Section: Air Ions In the Environmentmentioning
confidence: 99%
“…For example, systems for generation of NAI can be broadly divided into water-generated NAI systems based on the Lenard effect and electrically-generated NAI systems using corona discharge, and it has been suggested that water-generated NAI have a longer lifetime after generation and more beneficial effects on autonomic regulation, immunologic activation, and aerobic metabolism (Ryushi et al 1998;Iwama 2004;Yamada et al 2006). In addition, it has been reported that exposure to large quantities of NAI (>300,000 NAI cm −3 ) injures tissue possibly as a result of generation of superoxide (Yates et al 1986;Goldstein and Arshavskaya 1997).…”
Section: Discussionmentioning
confidence: 99%